XVIII International Youth Scientific School "Coherent Optics and Optical Spectroscopy" - Salakhov, M Kh; Samartsev, V V; Gainutdinov, R Kh (Journal of physics. Conference series, 2015)
Kazan Federal University has held the annual International Youth School "Coherent Optics and Optical Spectroscopy" since 1997. The choice of the topic is not accidental. Kazan is the home of photon echo which was predicted at Kazan Physical-Technical Institute in 1963 by Prof. U.G. Kopvil'em and V.R. Nagibarov and observed in Columbia University by N.A. Kurnit, I.D. Abella, and S.R. Hartmann in 1964. Since then, photon echo has become a powerful tool of coherent optical spectroscopy and optical information processing, which have been developed here in Kazan in close collaboration between Kazan Physical-Technical Institute and Kazan Federal University. The main subjects of the XVIII International Youth School are: Nonlinear and coherent optics; Atomic and molecular spectroscopy; Coherent laser spectroscopy; Problems of quantum optics; Quantum theory of radiation; and Nanophotonics and Scanning Probe Microscopy. The unchallenged organizers of that school are Kazan Federal University and Kazan E.K. Zavoisky Physical-Technical Institute. The rector of the School is Professor Myakzyum Salakhov, and the vice-rector is Professor Vitaly Samartsev. The International Youth Scientific School "Coherent Optics and Optical Spectroscopy" follows the global pattern of comprehensive studies of matter properties and their interaction with electromagnetic fields. Since 1997 more than 100 famous scientists from the USA, Germany, Ukraine, Belarus and Russia have given plenary lecture presentations. Here over 1000 young scientists had an opportunity to participate in lively discussions about the latest scientific news. Many young people have submitted interesting reports on photonics, quantum electronics, laser physics, quantum optics, traditional optical and laser spectroscopy, non-linear optics, material science and nanotechnology. Here we are publishing the fullsize papers prepared from the most interesting lectures and reports selected by the Program Committee of the School. The International Youth Scientific School "Coherent Optics and Optical Spectroscopy" was greatly supported by The Optical Society of America, the Russian Foundation for Basic Research, the non-profit Dynasty Foundation, the Tatarstan Academy of Science, and the Ministry of Education and Science of the Russian Federation. It is a pleasure to thank the sponsors and all the participants and contributors who made the International School meeting possible and interesting.